THE DESTRUCTIVE INFLUENCE OF VICTORIAN MRALITY ON INDIVIDUAL FREEDOM AND HUMAN POTENTIAL (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Thomas Hardy’s Jude the Obscure (1895) stands as one of the most This article explores Thomas Hardy’s Jude the Obscure (1895) as a critique of Victorian morality, examining how rigid social, religious, and ethical codes constrained personal freedom, emotional fulfillment, and intellectual ambition. The study analyzes Hardy’s treatment of marriage, sexuality, and social conformity, showing how these institutions functioned to enforce societal expectations rather than nurture human relationships. It investigates the psychological and emotional consequences of moral repression, particularly the impact of gender inequality and class hierarchy on the protagonists, Jude Fawley and Sue Bridehead. The article also considers the role of religion as a mechanism of control and the broader social critique embedded in Hardy’s narrative. By highlighting the conflict between individual conscience and societal orthodoxy, this study demonstrates how Jude the Obscure functions as a powerful work of protest against the moral absolutism of Victorian England.